Marine internet:strategies,tactics and challenges - Shengming JIANG (Dianxin kexue)
The marine internet is an extension of the terrestrial internet in the marine environment (underwater,water and air) and its importance is self-evident.However,the huge differences between land and sea make it impossible for the terrestrial internet to directly and seamlessly expand into the marine environment,and lead to some mature network research ideas and design methods becoming inapplicable.The strategic significance,status quo,tactics and major challenges of the marine internet were discussed briefly.